"Free Means Libre": Racialization of Arts in Madrid and Latin American Resilience through Performance. Issue 1 (April 2015) - Montalvo Chaves, Angeles
Abstract In Madrid, members of the theater company Entrecalles, which had been formed mainly by Latin American artists, experienced serious racial forms of marginalization. Through their phenotypic traits, their corporeal differentiation as Indigenous and Metizos evinces racist definitions under postcolonialism. This case study ties cultural resilience to political agendas and connects "citizenship status" to "citizenship artistic presence." By exploring the extent to which immigrant regulations can deprive Entrecalles artists of full citizenship in governmental domains, the article exposes the existing interrelationship between their performances and their presence as citizens in the city. Their efforts to sustain artistic practices beyond non‐institutionalized spheres reveal institutional boundaries that pose difficulties for their public expression. However, the intercultural dialogues they maintain regarding libre arenas enable them to negotiate a "creation of spaces" which connect capital resources and city itineraries, and to emerge as political and artistic citizens.